The interplay between the gut-brain axis and the microbiome: A perspective on psychiatric and neurodegenerative disorders - Bashir, Yasir; Khan, Asad U. (Frontiers in Neuroscience, 2022)
What is the effect of our gut microbial flora on brain? Does the gut microbiome have any role in the causation of psychiatric and neurodegenerative diseases? Does the effect of gut microbiota traverse the gut-brain axis? Questions like these have been irking the scientific fraternity for quite some time now. Research in the quest for answers to these questions, to unravel the potential role of the microbiota inhabiting the gut in controlling brain functions, has progressed manifold over the last two decades. Although the possibility of microbiome as the key susceptibility factor for neurological disorders viz. Parkinson’s disease, Alzheimer’s disease, multiple sclerosis, and autism spectrum disorder has bolstered by an increase in the clinical and preclinical evidence, the field is still in its infancy. Given the fact that the diversity of the gut microbiota is affected by various factors including the diet and exercise, the interpretation of such data becomes all the more difficult. Also, such studies have been mostly conducted on animal models, so there is a need for randomised controlled trials in human subjects, corroborated by longitudinal studies, to establish if modulating the gut microbiota can unravel novel therapeutic interventions. Exploring the systems biology approaches to integrate such data with genomic, metagenomic and metabolomic data from clinical subjects with psychiatric and neurological diseases can prove to be a helpful guide in individual treatment selection.